2021
DOI: 10.1097/tp.0000000000004021
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Humoral Response to Third Dose of BNT162b2 mRNA COVID-19 Vaccine Despite Detectable Spike Protein–specific T cells in Lung Transplant Recipients

Abstract: J.H. and T.K. had full access to all of the data in the study and take responsibility for the integrity of the data and the accuracy of the data analysis, and they participated in drafting of the article, statistical analysis, and data visualization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
1
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 5 publications
(10 reference statements)
4
23
1
2
Order By: Relevance
“… 5 , 6 , 7 , 8 , 9 , 10 , 11 Previous studies showed that around half of solid organ recipients who were non-responders to the second dose seroconverted after a third mRNA vaccine dose, given as booster. 12 , 13 , 14 , 15 However, only few studies have determined the effectiveness of a third vaccine dose in LTR, 16 , 17 and markers predictive of vaccine response are still lacking. In order to quantify the impact of immunosuppression on vaccine response and hopefully to predict response or nonresponse, one should be able to quantify the level of immunosuppression.…”
Section: Introductionmentioning
confidence: 99%
“… 5 , 6 , 7 , 8 , 9 , 10 , 11 Previous studies showed that around half of solid organ recipients who were non-responders to the second dose seroconverted after a third mRNA vaccine dose, given as booster. 12 , 13 , 14 , 15 However, only few studies have determined the effectiveness of a third vaccine dose in LTR, 16 , 17 and markers predictive of vaccine response are still lacking. In order to quantify the impact of immunosuppression on vaccine response and hopefully to predict response or nonresponse, one should be able to quantify the level of immunosuppression.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the observed serologic response in lung transplant recipients after two doses of an mRNA-based SARS-CoV-2 vaccine is poor [ 1 ]. It is recommended to give a third vaccine dose to all solid organ transplant recipients [ 2 ], but there are few reports on the serologic response to a third vaccine dose in lung transplant recipients specifically [ [3] , [4] , [5] ]. We previously reported on the serologic response to two doses of an mRNA-based SARS-CoV-2 vaccine in 91 lung transplant recipients [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the duration of detectable immune responses was comparable to that in a healthy population ( 14 16 ). Therefore, the biological drugs used to treat the patients in this study are different from other immunomodulatory drugs, which have been shown to compromise the immunogenicity of the COVID-19 vaccine ( 51 53 ).…”
Section: Discussionmentioning
confidence: 99%